2010
DOI: 10.1177/0886260510372945
|View full text |Cite
|
Sign up to set email alerts
|

Blaming the Victim and Exonerating the Perpetrator in Cases of Rape and Robbery: Is There a Double Standard?

Abstract: Research in legal decision making has demonstrated the tendency to blame the victim and exonerate the perpetrator of sexual assault. This study examined the hypothesis of a special leniency bias in rape cases by comparing them to cases of robbery. N = 288 participants received descriptions of rape and robbery of a female victim by a male perpetrator and made ratings of victim and perpetrator blame. Case scenarios varied with respect to the prior relationship (strangers, acquaintances, ex-partners) and coercive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
2
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(132 citation statements)
references
References 11 publications
10
113
2
7
Order By: Relevance
“…Conversely, participants tend to attribute less blame to perpetrators of acquaintance rape than perpetrators of stranger rape (Frese, Moya, & Medias, 2004;Viki et al, 2004). The closer the relationship, the less blame is attributed to the perpetrator and the more to the victim (Bieneck & Krah e, 2011). There are several explanations for why this might be, including attitudes relating to Ambivalent Sexism (AS) and Rape Myth Acceptance (RMA).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, participants tend to attribute less blame to perpetrators of acquaintance rape than perpetrators of stranger rape (Frese, Moya, & Medias, 2004;Viki et al, 2004). The closer the relationship, the less blame is attributed to the perpetrator and the more to the victim (Bieneck & Krah e, 2011). There are several explanations for why this might be, including attitudes relating to Ambivalent Sexism (AS) and Rape Myth Acceptance (RMA).…”
Section: Introductionmentioning
confidence: 99%
“…According to Lerner, the internal logic of the moral world is one of justice, where people get what they deserve and deserve what they get. Unfortunately, events like natural disasters and other varieties of seemingly senseless victimization do not always comport with this moral logic, and so maintaining belief in a just world sometimes requires people to construct narratives in which victims deserve the misfortunes that befall them [12][13][14].…”
Section: Moral Coherencementioning
confidence: 99%
“…It has been shown that victims who fail to engage in this behavior, by forgiving transgressions without blaming or without demanding an apology exhibit reduced self-respect-a phenomenon authors aptly call the "doormat effect" (Luchies et al, 2010). The tendency to "blame the victim," like, for instance, in cases of sexual assault (Bieneck & Krahé, 2011;George & Martínez, 2002;Idisis, BenDavid, & Ben-Nachum, 2007), may exacerbate this negative selfesteem impact for the victim. This provides a strong reason why victims value confessions or apologies from their abusers, and why apologies can reduce the victim's aggression and desire to punish the perpetrator (Abeler et al, 2010;Darby & Schlenker, 1982;Ho, 2012;Ho & Liu, 2011;Ohbuchi et al, 1989).…”
mentioning
confidence: 99%